2012
DOI: 10.1089/neu.2011.2105
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Suture Middle Cerebral Artery Occlusion Model in C57BL/6 Mice Circumvents Posterior Communicating Artery Dysplasia

Abstract: The suture middle cerebral artery occlusion (MCAO) model is used worldwide in both academia and industry. However, the variable occurrence of dysplasia in posterior communicating arteries (PcomAs) induces high mortality and instability in permanent MCAO models, limiting the model's application to transient focal ischemia. In particular, high mortality in intraluminal suture MCAO models is associated with the dysplasia of PcomAs in C57BL/6 mice. Optimization of silicone coating length is critical for reducing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 31 publications
(35 reference statements)
3
32
0
Order By: Relevance
“…44 Since then, numerous studies have studied the microstructure and function of much smaller cerebral vessels, primarily in rats 24,42,[45][46][47] and mice. 23,48,49 Again, the advantage of SR is that it can simultaneously image both pial (surface) and penetrating perforating vessels 23,42,45 because there is no single focal plane ( Figure 5). Therefore, vessels at different depths can be measured simultaneously without magnification artefacts or focal blurring.…”
Section: Cerebral Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Since then, numerous studies have studied the microstructure and function of much smaller cerebral vessels, primarily in rats 24,42,[45][46][47] and mice. 23,48,49 Again, the advantage of SR is that it can simultaneously image both pial (surface) and penetrating perforating vessels 23,42,45 because there is no single focal plane ( Figure 5). Therefore, vessels at different depths can be measured simultaneously without magnification artefacts or focal blurring.…”
Section: Cerebral Circulationmentioning
confidence: 99%
“…However, cerebral aneurysms of such traditional animal models are usually too small to be imaged in vivo with conventional CT. 50 SR microangiography has provided a novel means of identifying localized cerebral aneurysms 50 and differences in vascular reactivity after cerebral ischemia. 45,51 Moreover, the less invasive approach and detailed visualization of the cerebral arterioles mean SR can be used to confirm high reproducibility of experimentally induced cerebral vessel occlusion 47,49 and to repeatedly assess the morphological and functional changes of the cerebral vessels in vivo at regular intervals (eg, monthly) after induction of cerebral aneurysms or subarachnoid hemorrhage. As mentioned, spatial resolution is determined in part by the iodine concentration.…”
Section: Cerebral Circulationmentioning
confidence: 99%
“…Moreover, it is known that a slight difference in thread characteristics (diameter, tensile strength, and extensibility) causes great variability in infarct lesion volumes and their reproducibility [35], and there has been criticism that the data obtained using the ITI model are still far from being standardized worldwide [51]. Numerous modifications of occlusive thread have been reported, including the recent proposal that the length of the thread coating should be adjusted to avoid occlusion of the ipsilateral posterior communicating artery and the subsequent expansion of the ischemic lesion into the posterior cerebral artery territory that results in development of massive cerebral infarction and acute death in C57BL/6 mice [55,56]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, when larger sutures coating are used, the small arteries could be occluded. For instance, the study by Yuan et al, reported that using a filament with 4 mm coating could induce damage in the thalamus, hypothalamus, and hippocampus whereas when this suture was sustained with a 2 mm coating one, the three structures were intact (Yuan et al, 2012). In order to prevent the unintentional occlusion of arteries close to the MCA, the knowledge of the distance between the MCA and the AchA, VTA or LHA should be considered.…”
Section: Suture Coating and Depthmentioning
confidence: 99%
“…For instance, He et al have shown that the distance between the MCA and the AchA is about 1.75 mm in rat (He et al, 2000). In a mouse model of MCAO, Yuan et al determined that a coating length of 1.5 mm induces a reproducible infarct volume without unspecific lesions (Yuan et al, 2012), suggesting that the distance between the MCA and AchA is less than 1.5 mm. Accordingly, the choice of the thread coating length and its standardization seems to be crucial for the reproducibility of MCAO.…”
Section: Suture Coating and Depthmentioning
confidence: 99%